PENGARUH MODEL PEMBELAJARAN MUHIBBAH TERHADAP KESUKSESAN BELAJAR MAHASISWA - Moh Ali; A. Kumedi Ja'far (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACTThe success of the teaching and learning process is the ideal of the academic community regardless of their position. This success can be measured to the extent to wich each teacher is ebel to present teaching material properly and easily digensted by student as well,In edition to the ability and goog anderstanding of the subject they have, mastery of learning matterials, learning strategies ang edition to a sense of empathy, as wel as a wealth of ideas in the teaching –learning procces. One the Muhibbah lecture model is an educational model that focuses on how students enjoy and have fun interacting with their lecturers. Discussion , dialogue, visit to ech other, exemplay behavior ang maintaining togederness, unity and full of intimacy. Keywords: Good Lecture model Muhibbah.